ANALISIS PERSEPSI ANGGOTA TENTANG KUALITAS LAYANAN CU BANURI HARAPAN KITA DI BATANGTARANG - Wahyuni, Wahyuni; Khosmas, Khosmas; Genjik, Bambang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
Abstractthe title of this research is “the analysis of members perceptions of the quality of CU Banuri Harapan Kita at Batangtarang, Sanggau District. Problems in this study (1) What are the members' perceptions about the speed and timeliness of service? , (2) What are the members' perceptions of service hospitality?, (3) What are the members' perceptions about comfort in the services provided by Banuri Harapan Kita Credit Union employees in Batangtarang, Sanggau District District?. This study aims to analyze members' perceptions of the accuracy and speed of service time, analyze members' perceptions of Service Hospitality, analyze members' perceptions of Comfort in Obtaining Services.The focus of this research is the Perception of Members About the Quality of Service of Banuri Harapan Kita Credit Union in Batangtarang, Balai District, Sanggau District with sub-focus, that is:(1) Accuracy and Speed of Service Time, (2) Hospitality of Service, (3) Comfort in Obtaining Services. The research method used is descriptive method with a survey study form. The population in this study were 3,454 members of Banuri Harapan Kita Credit Union in Batangtarang, Balai District, Sanggau District. The research sample was 100 members. This research uses direct communication, indirect communication, and documentary studies. The data collection tool used is the interview guide, questionnaire, and notebook. The study was analyzed based on quantitative descriptive. The results of members' perceptions regarding the Accuracy and Speed of Service Time, Hospitality of Services, and Comfort in Obtaining Services are good. Judging from the members' answers to the question questionnaire more than 50% of the members answered well. The results showed that Member Perceptions of Service Quality of Banuri Harapan Kita CU In Batangtarang, Balai Sub-District, Sanggau District had a percentage of 73% in a high position. Keywords:Perception, Members, Service Quality